2015
DOI: 10.1037/ort0000019
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and guardianship: A moderated mediation analysis of predictors of post-permanency continuity.

Abstract: The original thinking behind permanency planning for foster children was to secure a caregiver's intention to provide a permanent home, not to guarantee it. Little is known, however, about how intentions change after permanence or what effect this change has on post-permanency continuity of care. This study examined the mediating effects of caregivers' thoughts about ending an adoption or guardianship, and how this mechanism may be contingent on primordial and bureaucratic factors that child welfare agencies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Most recently, an association between more placement moves while in OHC and an increased likelihood of an adoption, special guardianship or residence order breaking down have been described (Selwyn et al, 2014). Studies in other countries have described associations with re-entry to OHC and the child’s age at exit (Orsi, 2015; White, 2016; Yampolskaya, Armstrong, & Vargo, 2007), ethnicity (Orsi, 2015; Shaw, 2006), having behavioral or health problems (Barth, Weigensberg, Fisher, Fetrow, & Green, 2008; Liao & White, 2014; Testa, Snyder, Wu, Rolock, & Liao, 2015; White, 2016; Yampolskaya et al, 2007), a longer time spent in care (McDonald, Bryson, & Poertner, 2006; Wells & Guo, 1999), placement setting (Carnochan, Rizik-Baer, & Austin, 2013; Lee, Jonson-Reid, & Drake, 2012), and placement stability (Carnochan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, an association between more placement moves while in OHC and an increased likelihood of an adoption, special guardianship or residence order breaking down have been described (Selwyn et al, 2014). Studies in other countries have described associations with re-entry to OHC and the child’s age at exit (Orsi, 2015; White, 2016; Yampolskaya, Armstrong, & Vargo, 2007), ethnicity (Orsi, 2015; Shaw, 2006), having behavioral or health problems (Barth, Weigensberg, Fisher, Fetrow, & Green, 2008; Liao & White, 2014; Testa, Snyder, Wu, Rolock, & Liao, 2015; White, 2016; Yampolskaya et al, 2007), a longer time spent in care (McDonald, Bryson, & Poertner, 2006; Wells & Guo, 1999), placement setting (Carnochan, Rizik-Baer, & Austin, 2013; Lee, Jonson-Reid, & Drake, 2012), and placement stability (Carnochan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These data do not, for example, report on the support system of the child, if they are supported, emotionally or financially, by their birth parents, adoptive parents or legal guardians after state custody. Other studies report that most caregivers state that they have positive feelings towards the children they have adopted or assumed guardianship (Fuller et al, 2006;Testa et al, 2014). From these data it is unclear if the children would report the same feelings, or how those feelings impact continuity in caregiving.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…These data do not provide a reason that the subsidy stops, only the end date of the last payment. However, a systematic spot-check of these cases found that the children were no longer living in the home after the subsidy payment ended (Testa, Snyder, Wu, Rolock, & Liao, 2014). Approximately onethird (N ¼ 361) of these children also experienced the death of at least one caregiver.…”
Section: Reentered State Custody Predominately In Traditional and Kimentioning
confidence: 99%
See 1 more Smart Citation
“…Si atendemos a los factores del niño encontramos que los factores más claros de riesgo son la mayor edad del menor en el momento de la adopción, los problemas de conducta, especialmente los de tipo externalizante y los problemas en el área de la vinculación. Aunque el estudio de la historia previa del menor es más complejo, también existe cierto acuerdo en cuanto a que la adversidad de la historia previa y el mayor número de cambios en su historia de cuidado son factores que aumentan el riesgo de ruptura (Coakley y Berrick, 2008;Smith, Howard, Garnier y Ryan, 2006;Testa, Snyder, Wu, Rolock y Liao, 2015).…”
Section: La Prevención De Rupturas En El Trabajo Preadoptivounclassified